Efektivitas Pengetahuan dan Minat terhadap Keputusan Investasi pada Produk Deposito Syariah bagi Mahasantri Universitas Al-Amien Prenduan - Nor Aziza, Sitti (Institut Agama Islam YPBWI Surabaya, 2024)
This research aims to determine the influence of knowledge, interest and motivation of UNIA students on investment decisions in sharia deposit products and to find out whether motivation can moderate the relationship between knowledge and interest of UNIA students on investment decisions in sharia deposit products. This research uses a quantitative method consisting of 3 variables, namely variable X (knowledge and interest), variable Y (investment decisions on sharia deposit products), variable Z (motivation) as a moderating variable. For data analysis using validity and reliability tests, classical assumptions, multiple linear regression, F test, T test, R2 test and moderation regression test. From the results of data analysis, it shows that the knowledge variable has a calculated t value > t table (3.161 > 2.001), so knowledge has an influence on investment decisions in sharia deposit products, the interest variable has a calculated t value of (0.868 < 2.001), so interest has no influence on investment decisions in sharia deposit products, motivation t value > t table (2.026 > 2.001) partially that motivation has an influence on investment decisions in sharia deposit products, the motivation variable with knowledge has a t value of .043 with a significance of .967 (not significant) This means In this case, motivation cannot moderate the relationship between knowledge and investment decisions in sharia deposit products. The interaction variable between investment interest and motivation has a calculated t value of -.286 and is significant at .776 (not significant), meaning that in this case motivation cannot moderate the relationship between interest. on investment decisions in sharia deposit products.